1978
DOI: 10.1063/1.324560
|View full text |Cite
|
Sign up to set email alerts
|

Defect pairing diffusion, and solubility studies in selenium-doped silicon

Abstract: Se was diffused into Si doped with various concentrations of the group-III elements B, Ga, Al, or In. Selenium acting as a double donor in silicon is found to pair with all the acceptors from the group-III examined, and the Se-acceptor pairs give rise to a donor level at Ec−0.2 eV. An additional donor level at Ec−0.3 eV is assigned to the first ionization level of selenium in silicon. Solubility of Se in silicon in the temperature range 850–1300 °C has been established through Hall-effect measurements. The dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0
1

Year Published

1988
1988
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(25 citation statements)
references
References 4 publications
2
21
0
1
Order By: Relevance
“…The large number of impurity species we examine diffuse by a variety of mechanisms, 44,45 some of which change with temperature and some of which are unknown at the melting point. Hence 53 Au and Zn, 54 Co, 55 Cr, 56 Cu, 57 Fe, 58 Pt, 59 S, 60 Se, 61 Sn, 47 and Te. 62 Values for k e are values reported in: As, Bi, Cu, Ga, In, Sb, and Zn, 17 Au, 21 Co and Cr, 63 Fe, 64 S, 65 and Sn.…”
Section: Discussionmentioning
confidence: 99%
“…The large number of impurity species we examine diffuse by a variety of mechanisms, 44,45 some of which change with temperature and some of which are unknown at the melting point. Hence 53 Au and Zn, 54 Co, 55 Cr, 56 Cu, 57 Fe, 58 Pt, 59 S, 60 Se, 61 Sn, 47 and Te. 62 Values for k e are values reported in: As, Bi, Cu, Ga, In, Sb, and Zn, 17 Au, 21 Co and Cr, 63 Fe, 64 S, 65 and Sn.…”
Section: Discussionmentioning
confidence: 99%
“…The metastable solubility is the competition between the diffusive velocity of the impurity in the amorphous phase and the velocity of solid phase epitaxy, both of which depend on the temperature 32,36 . The impurities can be trapped into Si in this process, due to the high velocity (10 -1 -10 -3 m/s) of the amorphous-crystalline interface and the low diffusion velocity (10 -2 -10 -4 m/s) for FLA (for temperatures below 1300 °C) 10,37 . Thus, we can obtain the metastable solubility which is around one to two orders of magnitude larger than the maximum equilibrium solubility 32 .…”
Section: The Impurity Incorporation Of Ti Implanted Si Was Interpretementioning
confidence: 99%
“…To form such an impurity band instead of isolated levels, one needs to have doping concentrations far exceeding the Mott transition limit, which is ~5×10 19 cm -3 for Ti 7 . Unfortunately, most deep level impurities (Ti, S and Se) have relatively low solubility in silicon [8][9][10] . As an industry-standard method, ion implantation works in non-thermal-equilibrium regime and can overcome the thermal solubility limit.…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, it has recently been demonstrated that millisecond range flash-lamp annealing (FLA) induces solid phase epitaxy which accounts for a complete recrystallization of the implanted layer at annealing temperatures below the melting point of substrate [20][21][22]. During this process, the impurities have more probability to be incorporated into the semiconductor lattice due to i) the high velocity of the solidification during recrystallization after FLA and ii) the low diffusion velocity of impurities in the solid phase [23,24]. It has been shown that FLA is superior to laser annealing in preventing the surface segregation of dopants and in suppressing the cellular breakdown for semiconductors with high impurity concentration [25,26].…”
Section: Introductionmentioning
confidence: 99%